Recitation Of Ayat Al- Hirzi As Santri Protection at Raudhatul Jannah Boarding School Palangka Raya - Safri Saputra; Akhmad Supriadi; Munirah; Rafi’i (al-Afkar, Journal For Islamic Studies, 2024)
The purpose of this study is to elaborate on the phenomenon of living Qur'an, namely the reading of Ayat Al-Hirzi at the Raudhatul Jannah Islamic Boarding School Palangka Raya which is a mandatory program for students, explaining the practice and explaining the meaning of Ayat Al-Hirzi according to the male students and ustadz of the Raudhatul Jannah Islamic Boarding School Palangka Raya. This research is a type of field research with qualitative methods and uses the theory of functional reception of the Quran in analyzing data. The results showed that the recitation of Ayat Al-Hirzi istiqamah is an effort in an effort to protect the students' selves while in the Islamic Boarding School, besides that Ayat Al-Hirzi also has values in its reading, namely as a means to make remembrance to Allah Almighty, facilitate the cottage program, be protected from outside influences and can help students in maintaining memorization of the Qur'an. The recitation of Ayat Al-Hirzi has a positive impact on the practitioner both outwardly and mentally, in the form of a sense of security and protection from unwanted things that can happen anywhere and anytime and get a sense of peace and a calm soul.